2012
DOI: 10.1002/ijc.27898
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking and risk of multiple myeloma: A meta‐analysis of 40 observational studies

Abstract: This meta-analysis aims to quantitatively synthesize all available data on the association between tobacco smoking and multiple myeloma (MM) risk. Eligible studies were identified and pooled effect estimates (odds ratios and relative risks) were calculated regarding ever, current and former smoking. Separate analyses were performed on case-control and cohort studies, as well as on males and females. Meta-regression analysis with percentage of males, mean age, years of smoking, pack-years, cigarettes per day, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
5
15
0
4
Order By: Relevance
“…67 Regarding the spectrum of lifestyle parameters, both overweight and obesity correlated with increased MM incidence and mortality 51 ; the underlying explanations may involve modified IGF-1, 68 adiponectin, 69 inflammatory cytokine 70 levels, or adipocyteebone marrow cell interactions. 71 On the other hand, smoking 42 and physical activity 36 were not significantly associated with MM risk. The potential protective effects of alcohol consumption on MM risk 61 have been attributed to its immunomodulatory effects [72][73][74] or its inhibition through ethanol on the mammalian target of rapamycin signaling.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…67 Regarding the spectrum of lifestyle parameters, both overweight and obesity correlated with increased MM incidence and mortality 51 ; the underlying explanations may involve modified IGF-1, 68 adiponectin, 69 inflammatory cytokine 70 levels, or adipocyteebone marrow cell interactions. 71 On the other hand, smoking 42 and physical activity 36 were not significantly associated with MM risk. The potential protective effects of alcohol consumption on MM risk 61 have been attributed to its immunomodulatory effects [72][73][74] or its inhibition through ethanol on the mammalian target of rapamycin signaling.…”
Section: Discussionmentioning
confidence: 90%
“…51 On the other hand, the inverse association between physical activity and MM risk did not reach statistical significance 36 ; similarly, no significant association implicated ever or current smoking. 42 An overall protective association was noted with respect to ever alcohol consumption, which was particularly evident at the assessment of wine intake and in the subpopulation of women. 61 …”
Section: Psaltopoulou 2014 61mentioning
confidence: 96%
“…Although the relations of physical activity to hematologic cancer subtypes did not vary according to smoking, in a subanalysis of total hematologic cancer, we found that studies that adjusted for smoking showed a stronger inverse association with physical activity than studies that did not adjust for smoking. Smoking is inversely related to physical activity (55) and positively associated with all investigated hematologic cancer subtypes (56-58) except multiple myeloma (59). Thus, adjustment for smoking would be expected to produce a less pronounced inverse association between physical activity and total hematologic cancer than not adjusting for smoking.…”
Section: Discussionmentioning
confidence: 97%
“…The etiology of this malignancy remains poorly understood. Past investigations of cigarette smoking and multiple myeloma have generally yielded null results (1, 2), although most studies have been underpowered to detect moderate associations, particularly within population subgroups. To clarify the relationship between cigarette smoking and multiple myeloma, we conducted a pooled analysis of case-control studies participating in the International Multiple Myeloma Consortium (IMMC).…”
Section: Introductionmentioning
confidence: 99%